Accompanying professional teachers to transfer knowledge in Higher Vocational Education: the contributions of Professional Didactics and Cultural Historical Activity Theory - Pacquola , Mariachiara; Migliore , Maria Cristina (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
The aim of this article is to contribute to strengthening the relationship between training and work, in particular by rethinking training and didactic design in the Italian Higher Vocational Education system (ITS). For the purposes of a training and didactic design capable of respond-ing effectively to the actual skill requirements of work contexts, a space for dialogue is high-lighted between two theoretical approaches, both oriented towards activity analysis: Profession-al Didactics (DP) and Cultural Historical Activity Theory (CHAT). If the former is oriented towards eliciting the tacit knowledge possessed by professionals at work, considering socio-technical and ergonomic aspects in the analysis of the work situation, the perspective of the lat-ter approach focuses on the relevance of production strategies and motives/reasons in shaping collective activities and tacit knowledge at work. Both can contribute, therefore, to highlighting not only the importance that the contents of the professional knowledge to be taught are devel-oped from the effective knowledge of work, but also that the didactic transposition of this knowledge considers the ways and contexts in which it was learned and will be used. In con-clusion, it emerges that the collaboration between higher vocational education centres and enter-prises is crucial in order to create the conditions for professionals to become do-cents through the elicitation of their tacit knowledge.